Acute oxygen use in hospitalised patients with chronic obstructive pulmonary disease is guideline discordant. Issue 5 (27th May 2021) - Deshpande, Sheetal; Datey, Nainika; Liacos, Alexandra; Joosten, Simon A.; Leong, Paul
Abstract: Ample evidence supports an association between acute oxygen over‐administration and harm. Australian and international guidelines consistently recommend lower oxygen saturation aims in populations with chronic obstructive pulmonary disease (COPD). We assessed adherence to acute oxygen use guidelines and outcomes in hospitalised patients with COPD at a large Australian metropolitan hospital network.